State-of-the-Art Environmental Chemicals Exposomics and Metabolomics (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This Special Issue contains 13 articles—12 research papers and 1 review article. The 12 research papers focus on developing new methods for detecting specific chemical exposomes, exploring new aspects of exposome-related toxicity, applying metabolomics, and integrating metabolic information with exposomics and other omics across different biological layers in toxicology. The review article focuses on a neurotoxicity-related system linked to metabolism targeted by multiple chemicals. These articles advance our understanding of environmental chemical exposomes and metabolomics within toxicology.